2003
DOI: 10.1677/joe.0.1770017
|View full text |Cite
|
Sign up to set email alerts
|

The biological clock tunes the organs of the body: timing by hormones and the autonomic nervous system

Abstract: The biological clock, the suprachiasmatic nucleus (SCN), is essential for our daily well-being. It prepares us for the upcoming period of activity by an anticipatory rise in heart rate, glucose and cortisol. At the same time the 'hormone of the darkness', melatonin, decreases. Thus, the time-ofday message penetrates into all tissues, interestingly not only by means of hormones but also by a direct neuronal influence of the SCN on the organs of the body. The axis between the SCN and the paraventricular nucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
207
0
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(223 citation statements)
references
References 59 publications
5
207
0
7
Order By: Relevance
“…As suggested by neuroanatomical studies (47,48), the SCN regulates peripheral circadian clocks by direct neuronal input. However, sympathetic inputs from the SCN alone cannot account for all circadian activities.…”
Section: Discussionmentioning
confidence: 98%
“…As suggested by neuroanatomical studies (47,48), the SCN regulates peripheral circadian clocks by direct neuronal input. However, sympathetic inputs from the SCN alone cannot account for all circadian activities.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding entrainment mechanisms by hormones, glucocorticoids play an important role. Plasma glucocorticoid concentration is regulated in a rhythmic fashion via the hypothalamus/pituitary/adrenal axis with contribution of the SCN (reviewed in Buijs et al, 2003). The glucocorticoid hormone analog dexamethasone synchronizes the oscillators of cultured cells (Balsalobre et al, 2000).…”
Section: Synchronization Of the Liver Oscillator By Systemic Timing Cuesmentioning
confidence: 99%
“…This presents an enlarged pool of factors within cells and tissues whose function could be compromised by circadian disruption. To add to this complexity, physiological rhythms, including endocrine function, are well documented (12,13). It has been shown that some of these endocrine signals can feedback to modulate circadian behavior and the SCN (14), whereas others, such as the glucocorticoids, modulate peripheral oscillators and have little effect on the SCN (15).…”
mentioning
confidence: 99%